2014
DOI: 10.1111/nyas.12408
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin D receptor turns off chronically activated T cells

Abstract: T cell proliferation and T helper (TH ) cells that make IL-17 (TH 17 cells) and IFN-γ (TH 1 cells) have been shown to be inhibited by 1,25(OH)2 D3 . Previous work has shown that immune-mediated diseases, where TH 1 and TH 17 cells are pathogenic, are ameliorated with 1,25(OH)2 D3 treatment. Paradoxically, infectious diseases that require TH 1 and TH 17 responses for host resistance are unaffected by 1,25(OH)2 D3 treatment. Resting T cells are not responsive to vitamin D because they do not express the vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 46 publications
4
69
0
Order By: Relevance
“…However in autoimmune disease, the T-cells continue to recognize an antigen and therefore continue to produce inflammatory cytokines. 14 The ability of calcitriol to turn off inflammation in autoimmune disease was shown with the EAE mouse model study, where isolated neural antigen-sensitized spleen cells produced significantly less IFN-g. 16 One mechanism for the decrease in IFN-g production is the simple fact that STAT1 becomes dephosphorylated, thus inactivated, and can no longer bind the response element for the IFN-g gene to cause transcription. Another mechanism is that VDR-RXR can bind the promoter of IL-2 36 or IFN-g, 37 showing direct repression of these inflammatory cytokines is possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However in autoimmune disease, the T-cells continue to recognize an antigen and therefore continue to produce inflammatory cytokines. 14 The ability of calcitriol to turn off inflammation in autoimmune disease was shown with the EAE mouse model study, where isolated neural antigen-sensitized spleen cells produced significantly less IFN-g. 16 One mechanism for the decrease in IFN-g production is the simple fact that STAT1 becomes dephosphorylated, thus inactivated, and can no longer bind the response element for the IFN-g gene to cause transcription. Another mechanism is that VDR-RXR can bind the promoter of IL-2 36 or IFN-g, 37 showing direct repression of these inflammatory cytokines is possible.…”
Section: Discussionmentioning
confidence: 99%
“…11 In the early 1980s, it was shown that calcitriol inhibited proliferation in phytohemagglutinin (PHA)-activated PBMCs, partially due to suppression of interleukin-2 (IL-2) production. 13 Cantorna and Waddell recently published a review of the evidence that vitamin D and VDR are needed to turn off chronically activated T-cells, 14 which is particularly applicable to T-LGLL, given that the T-LGLs are constitutively activated T-cells. Therefore, the literature clearly shows that calcitriol can act on T-cells and regulate processes other than calcium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…During the 1980s vitamin D receptors were identified on cells of the immune system (53,54) sparking interest in immunemodulating effects of vitamin D. For IBD, there is a compelling body of evidence from animal models that vitamin D has the capacity to alter immune responses (11,(55)(56)(57) . Vitamin D deficiency, for example, accelerates the development of experimental colitis in IL-10 knock-out mice, (12) whereas treatment with dietary vitamin D and calcium appear to protect against the development of inflammation (58) .…”
Section: Vitamin D Status and Associations With Disease Severity In Cmentioning
confidence: 99%
“…The inhibitory effects of 1,25(OH) 2 D on T cell production of IL-17, IFN-␥, and IL-2 are identical in human and mouse cells (11,12,24,25). The induction of FoxP3 ϩ T reg cells by 1,25(OH) 2 D has also been demonstrated to occur in human and mouse T cells (11,12,24,25). Some pathways are not identical; for example, the 1,25(OH) 2 D-induced production of cathelicidin occurs only in human but not mouse macrophages (2).…”
Section: Vitamin D and Human Pulmonary Infectionmentioning
confidence: 99%